(untitled) - Robert W July (Prospect Hights, Illinois, 1992)
The book offers an understanding of Africa, past and present. This history, therefore, though basically chronological, deals with themes that cut across time and place to furnish their own unity and consistency. Ther is, for example, migration - the vast movements of peoples, most notably by Nilotes and the Bantu. Ther is the power of religion, particularly in those upheavals that have periodically convulsed savanna populations ever since the advent of Islam. There is the 500-year interval of that uncertain romance between Africa and Europe that has so greatly influenced events in both continents and in the Americas. The book is divided into four parts. Part One, Ancient Africa, is concerned primarily with traditional Africa societies. Part Two appears under the title Revolutionary Africa, to emphasize those important developments across the continent that characterized the nineteeth century. Part Three, Colonial Africa, covers the brief but pivotal era of colonial control, leading to Part Four, Independent Africa, now a history in its own right, fully a generation old. Each chater provides suggestions for additional reading for those who wish to explore further
Keywords: africa - history